“Prácticas De Las Normas De Bioseguridad Y Su Incidencia Con Los Riesgos Laborales Biológicos Del Personal De Salud Del Area De Clinica. Hospital General Naval Guayaquil (Hosnag) - MayorgaLopez, Jenny Maricela (2015)
This thesis aims to determine the level of knowledge and application of biosecurity measures having staff area HOSNAG Clinic General Hospital. Materials and methods. An investigation was conducted: Exploratory, explanatory, cross, with a sample of 67 people. The information was collected through survey and observation guide, which was analyzed by means of tabulations and graphical representations. Results. Staff Clinic area HOSNAG General Hospital, has a medium-high knowledge which corresponds to 58% against the knowledge medium low 42%, poor enforcement against this knowledge, a percentage that endanger health personnel . Conclusion. It was identified that the main biosecurity measures are: barrier methods, proper disposal of contaminated material, proper management of stab elements hand washing are not being correctly applied by the entire team of health of the institution, making these situations a risk factor for an accident occur. Recommendation. Strengthen the theoretical concepts and applicability of biosafety standards in biological occupational risk awareness among staff and achieve a habit of prevention.